Analisis Konten Nilai-Nilai Pai Pada Akun Tiktok Husain Basyaiban - Unik Hanifah Salsabila; Ahmad Paisol Putra; Riyanih Riyanih; Mirna Fadila Safitri; Dewi Roro Nur (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Husain Basyaiban is a content creator who is active on Tiktok, with Islamic preaching material content which is often uploaded to his Tiktok account. The da'wah topics created are quite varied, but still in accordance with the current situation in society. Husain's easy and interesting explanations make the content he creates very popular with many people. This research aims to understand and analyze the response of viewers or the public to the content created by Husain Basyaiban on his account @Kadamsidik00. The method used in this research is qualitative with a descriptive analysis approach. The results of this research show that the content created and uploaded by Husain Basyaiban since early 2022 has received a lot of positive responses from viewers. One of the preaching content with the theme of mandatory bathing that he uploaded received a very good response from viewers.